IMPROVEMENT OF INNOVATIVE TRAINING OF ROAD SPECIALISTS - I. I. Leonovich; S. V. Bogdanovich; I. V. Nesterovich (Наука и техника)
Complicated conditions, under which road enterprises of the Republic are forced to operate, put forward and reveal the necessity to innovative way of development. In order to fulfill this task it is necessary to have specialists who are capable and ready to realize this endeavour. The most acceptable variant is to train specialists who will be able to introduce innovations and who are presently involved in the production process. Such training should be carried out within the framework of post-graduate education. Authors have provide a number of reasons in favour of quick development of such education.